The development of women`s athletics: findings of an empirical analysis - Emrich, E.; Anthonj, P.; Flatau, J.; Hämmerle, M.; Rohkohl, F. (Schriften des Europäischen Instituts für Sozioökonomie e. V., 5, 2013)
The present survey measured a wide variety of indicators on different levels, which permit an evaluation of the development of the participation of women in athletics. All in all an upward trend can be?noted. One exception is the decreasing proportion of women on the ITO panels. The proportion of female athletes has remained constant over the?last few years, however already on a fairly high, if not yet equal,level to that of male athletes. In many fields, on the other hand,?despite the outlined development equal representation of women in athletics is still a long way off. (Originaltext universaar)